PENGARUH WAKTU TANAM, PEMBERIAN MULSA JERAMI DAN PENANAMAN REFUGIA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) VARIETAS NK 6326, HAMA DAN PATOGEN PENYAKIT SERTA MUSUH ALAMINYA - Rejo Wagiman; Yohanes Hendro Agus (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
Research on the effect of planting times, using straw, and planting refugia against growth and yield of corn (Zea mays L.) NK 6326variety, it’s pest and diasaes and natural enemies had been conducted in Tulung sub-district, Klaten district, Central Java province.The purpose of this research was to determine the effect of two different planting time based on “pranata mangsa” time (local wisdom) and farmer’s planting time which were combined with using straw and planting refugia against growth and yield of corn, it’s pest and diseases, it’s natural enemies population. This research used a Strip Plot Design with two main treatments with four additional treatments, and five replications. The main treatments were planting time based on farmer habit (A1) and planting time bades on “pranata mangsa” or ancient local wisdom (A2). Additional treatments included: using straw mulch and planting “refugia” (B1), using only straw mulch (B2), planting only “refugia” (B3), and without using straw mulch and without planting “refugia” (B4). The result of the experiment were analyzed by using the Analysis of Variance (ANOVA) and the Honestly Significance Difference (HSD) test at 95% confidence level. The result of this research showed that: (1) planting time based on farmer’s habit were higher than the planting time based on “pranata Mangsa” against plant height, wet weight of mass, dry weight of mass, weight of seded per cob, weight of seed per plot seed weight per hectare, and 1000 grains weight,(2) planting time based on farmer’s habit combined with using straw mulch and planting “refugia” were higer than planting time based on “pranata mangsa” combined with using straw mulch and palnting refugia against plant height, cob length, wet weight of mass, dry weigt of mass, total number of seed per ear, weight of seeds per cob, weight seeds per plot, weight of seed per hectare, and weight of 1000 grains, (3) planting refugia can increase the natural enemy population.